Subversion of the Immune Response by Human Pathogenic Mycoplasmas - Qin, Lianmei; Chen, Yiwen; You, Xiaoxing (Frontiers in Microbiology, 2019)
Mycoplasmas are a large group of prokaryotes which is believed to be originated from Gram-positive bacteria via degenerative evolution, and mainly capable of causing a wide range of human and animal infections. Although innate immunity and adaptive immunity play crucial roles in preventing mycoplasma infection, immune response that develops after infection fails to completely eliminate this bacterium under certain circumstances. Thus, it is reasonable to speculate that mycoplasmas employ some mechanisms to deal with coercion of host defence system. In this review, we will highlight and provide a comprehensive overview of immune evasion strategies that have emerged in mycoplasma infection, which can be divided into four aspects: (i) Molecular mimicry and antigenic variation on the surface of the bacteria to evade the immune surveillance; (ii) Overcoming the immune effector molecules assaults: Induction of detoxified enzymes to degradation of reactive oxygen species; Expression of nucleases to degrade the neutrophil extracellular traps to avoid killing by Neutrophil; Capture and cleavage of immunoglobulins to evade humoral immune response; (iii) Persistent survival: Invading into the host cell to escape the immune damage; Formation of a biofilm to establish a persistent infection; (iv) Modulation of the immune system to down-regulate the intensity of immune response. All of these features increase the probability of mycoplasma survival in the host and lead to a persistent, chronic infections. A profound understanding on the mycoplasma to subvert the immune system will help us to better understand why mycoplasma is so difficult to eradicate and ultimately provide new insights on the development of therapeutic regimens against this bacterium in future.